Inactivation of ccmO in Synechococcus sp. Strain PCC 7942 Results in a Mutant Requiring High Levels of CO(2) - Marco, E. (1994)
Inactivation of ccmO in Synechococcus sp. strain PCC 7942 resulted in a mutant which possesses aberrant carboxysomes and a normal inorganic carbon uptake capability but a reduced ability to photosynthetically utilize the internal inorganic carbon pool. Consequently, it exhibits low apparent photosynthetic affinity for extracellular inorganic carbon and demands high levels of CO(2) for growth.